Karyotype of Hairless Guinea pig - fatemeh Todehdehghani; Mohammah hassan motedayen; Shohreh Teimorzadeh (Journal of Sciences, Islamic Republic of Iran)
Chromosomal patterns of experimental animals are useful tools for cytogenetics research and animal breeding. Chromosome investigations of the hairless guinea pig are rare, therefore, karyotype of hairless guinea pigs (twelve male and female) was studied using metaphase spreads of bone marrows and G banding techniques. The chromosomes diploid number was 2n= 64 and polymorphism of three type chromosomal pairs were observed in the genus Cavia of Iranian hairless guinea pigs. A karyotype of 24 biarmed pairs and seven pairs of acrocentric chromosomes, 2 of sex chromosomes were also seen. The findings describe the karyology of the hairless guinea pig that is produced by Razi vaccine and serum research institute of Iran that improves our knowledge about laboratory hairless guinea pig and provides basic data for further use of the animal.